2002
DOI: 10.1152/jn.2002.88.4.1634
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Synchronization of γ and β Oscillations and the Plasticity of Excitatory and Inhibitory Synapses: A Network Model

Abstract: The ability of oscillating networks to synchronize despite significant separation in space, and thus time, is of biological significance, given that human γ activity can synchronize over distances of several millimeters to centimeters during perceptual and learning tasks. We use computer simulations of networks consisting of excitatory pyramidal cells (e-cells) and inhibitory interneurons (i-cells), modeling two tonically driven assemblies separated by large (≥8 ms) conduction delays. The results are as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
70
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 58 publications
9
70
1
1
Order By: Relevance
“…This result is consistent with previous findings of widespread, high-amplitude LFP oscillations transiently synchronized in sensorimotor areas during sensorimotor tasks (4,11), and with models indicating that beta oscillations are particularly well suited to support interactions between widespread cortical areas (20,21). By distinguishing between large-scale network synchrony due to driving and that due to mutual interactions, Granger causality analysis provided a deeper understanding of cortical interaction patterns than could be obtained from correlation or coherence measures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with previous findings of widespread, high-amplitude LFP oscillations transiently synchronized in sensorimotor areas during sensorimotor tasks (4,11), and with models indicating that beta oscillations are particularly well suited to support interactions between widespread cortical areas (20,21). By distinguishing between large-scale network synchrony due to driving and that due to mutual interactions, Granger causality analysis provided a deeper understanding of cortical interaction patterns than could be obtained from correlation or coherence measures.…”
Section: Discussionsupporting
confidence: 90%
“…It has long been proposed that behavior of this type depends on a corticoperipheral cortical sensorimotor loop (17,18), and more recently that this loop is supported by oscillatory neuronal activity (19). Reports of beta oscillations in both somatosensory and motor cortices during premovement maintenance behavior (3,5,6,9), taken together with recent studies proposing that beta rhythms are uniquely suited for synchronization over long conduction delays (20,21), thus suggest the hypothesis that beta oscillations provide a mechanism that binds sensory and motor cortical areas into a functioning loop.…”
mentioning
confidence: 99%
“…Electrical communication between interneurons has been demonstrated to be essential for the generation of gamma waves (Katsumaru et al, 1988;Gibson et al, 1999;Tamas et al, 2000), thereby supporting a role for interneuronal gap junctions at producing fast rhythmic synchronization in small patches of nervous tissue . Gamma oscillations are relevant in neuronal communication and synaptic plasticity (Bibbig et al, 2002), providing cues for understanding neuronal processing in both local and distributed cortical networks involved in cognitive functions (Jensen et al, 2007). Hypothetically, the lack of tau in neocortical regions and hippocampus might affect the maturation of parvalbumin interneurons involved in gamma synchronization within local neocortical circuits and/or the proper functioning of gap-junction channels in hippocampal networks.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, hippocampal theta oscillations have been found to drive processing in the prefrontal cortex (Jensen 2005), and several studies have suggested that gamma oscillations nested within theta (4-12 Hz) oscillations play a role in working memory functions (Jensen and Lisman 2005). Also, substantial recent data suggest that corticothalamic (Llinas et al 1998;Llinas and Ribary 2001;Neuenschwander et al 2002;Ribary 2005) and hippocampal networks (Buzsaki 1997;Harris et al 2003) make use of beta band (12-30 Hz) and gamma band (30-100 Hz) activity for long-distance transmission of information among task-related brain sites, although a number of those studies were carried out in brain slices or models (Kopell et al 2000;Bibbig et al 2002;Klausberger et al 2003;Olufsen et al 2003). These results suggest that task-related brain regions with differing network and cellular architectures may nonetheless display enhanced beta and gamma oscillations during attention to, and recognition of a rewarded stimulus, but to our knowledge this hypothesis had never been explicitly tested.…”
Section: Introductionmentioning
confidence: 99%